Phosphonium-iodonium ylides with heteroatomic groups in the synthesis of annelated P-containing heterocycles - Matveeva, Elena D.; Podrugina, Tatyana A.; Taranova, Marina A.; Vinogradov, Dmitriy S.; Gleiter, Rolf; Zefirov, Nikolay S. (The journal of organic chemistry, 2013)
The preparation and chemistry of novel sulfonyl- and phosphoryl-derived λ3-iodanes are reported. These compounds with three different heteroatoms attached to a negatively charged C atom represent potentially useful reagents that combine in one molecule the synthetic advantages of a phosphonium ylide and an iodonium salt. Specifically, they can react with a number of acetylenes, leading to hitherto unknown sulfonyl- and phosphoryl-substituted phosphinolines, phosphininothiophenes, and a novel type of annelated P-containing heterocycle—phosphininopyrazole.
Gesehen am 29.06.2021